Democratic Republic of the Congo : Technical Assistance Report-Financial Sector Stability Review. (IMF Staff Country Reports; Country Report ;, 2022)
In response to a request from the Central Bank of the Congo (BCC), the Monetary and Capital Markets Department of the International Monetary Fund (IMF) conducted a Financial Sector Stability Review (FSSR) mission virtually, during January 5-28, 2022. The FSSR performed a diagnostic of the financial system, reviewed progress in implementing previous IMF technical assistance (TA) recommendations, and developed a draft Technical Assistance Roadmap to help strengthen the BCC's capacity in the areas covered by the FSSR. The FSSR also for the first-time covered gender inclusion in financial supervision. It identified five macrofinancial vulnerabilities pertaining to: (i) the quality of the banking system's capital base; (ii) the difficulty in evaluating nonperforming loans following the COVID 19 financial support measures; (iii) risks related to financial dollarization; (iv) the impact on correspondent banking relationships of "de-risking"; and(v) intragroup exposures, as bank subsidiaries in the DRC place surplus funds with parent companies abroad. The BCC's adoption of COVID-19 exit measures in December 2021, including specific reporting requirements, should provide momentum for additional TA in the near term to help the BCC analyze banks' asset quality going forward.